X‐ray Photoelectron Spectroscopy of Pyridinium‐Based Ionic Liquids: Comparison to Imidazolium‐ and Pyrrolidinium‐Based Analogues. Issue 10 (7th May 2015) - Men, Shuang; Mitchell, Daniel S.; Lovelock, Kevin R. J.; Licence, Peter
Abstract We investigate eight 1‐alkylpyridinium‐based ionic liquids of the form [CnPy][A] by using X‐ray photoelectron spectroscopy (XPS). The electronic environment of each element of the ionic liquids is analyzed. In particular, a reliable fitting model is developed for the C 1s region that applies to each of the ionic liquids. This model allows the accurate charge correction of binding energies and the determination of reliable and reproducible binding energies for each ionic liquid. Shake‐up/off phenomena are determinedfor both C 1s and N 1s spectra. The electronic interaction between cations and anions is investigated for both simple ionic liquids and an example of an ionic‐liquid mixture; the effect of the anion on the electronic environment of the cation is also explored. Throughout the study, a detailed comparison is made between [C8Py][A] and analogues including 1‐octyl‐1‐methylpyrrolidinium‐ ([C8C1Pyrr][A]), and 1‐octyl‐3‐methylimidazolium‐ ([C8C1Im][A]) based samples, where X is common to all ionic liquids.